Examination of the physical condition management using salivary secretory immunoglobulin A for elite female sailing athlete - Shibata, S.; Tahara, R.; Hagiwara, M.; Watanabe, K.; Fujii, N. (Journal of High Performance Sport, 2023)
In this report, we performed a retrospective analysis of the relationship between salivary secretory immunoglobulin A (SIgA) and daily subjective conditions and changes in physical condition during the expedition period in sailing competitions. We performed continuous salivary SIgA measurements on one elite female windsurfing athlete over about 1.5 months, which included participation in two international competitions. The two international competitions and their preparatory periods were divided into phase 1 and 2, respectively. The salivary SIgA concentration was calculated using "SIgA simple detection kit" developed by us. We calculated salivary SIgA secretion by multiplying it with saliva secretion per minute. The subjective condition indicator and physical symptoms were input into the measurement iPod application. In phase 2, subjective complaints of URTI (Upper Respiratory Tract Infection) symptoms were observed for a total of 4 days. When salivary SIgA secretion was compared within phase 2 according to the presence or absence of URTI symptoms. Looking at the variation of salivary SIgA secretion, a decrease in salivary SIgA secretion was observed before complaining of subjective URTI symptoms. There was no clear association between subjective conditioning indicator and the salivary SIgA secretion. However, there were cases in which recovery of salivary SIgA occurred with a delay, and subjective complaints of URTI symptoms were subsequently observed, even though the sense of fatigue was improved by adjusting the exercise intensity. The windsurfing competitions are held in a natural environment where the climates are highly variables, and the travel time for games and training camps, and expedition periods are long, so maintaining the condition during the expedition has been an issue. From the results of this report, it is thought that the measurement of salivary SIgA over time as an objective indicator to monitor the state of fatigue is useful for maintaining good condition.